Agricultural Production Volume in Poland and in Belarus and its Prospects - Hrybau, Andrei; Hryshanava, Volha; Witkowska-Dąbrowska, Mirosława; Świdyńska, Natalia (Olsztyn Economic Journal, 2019)
The aim of this study was to identify changes in the agricultural production volume for selected branches in 2013-2017 and to estimate the future trends in Belarus and in Poland. The follow-ing comparative analyses used selected per capita intensity indices, thechange rate index and a logistic function. The study found that in both countries the greatest decrease took place in the plant production volume, while animal production volume remained more stable. The fact that its foreign trade is heavily dependent on Russia is the greatest problem for Belarus. Foreign trade in Poland is more stable and less dependent on Russia owing to the influence of the European Union.